2019
DOI: 10.3233/wor-192947
|View full text |Cite
|
Sign up to set email alerts
|

Selecting slip resistant winter footwear for personal support workers

Abstract: BACKGROUND:Falls are among the leading causes of occupational injuries for workers exposed to outdoor winter conditions such as Personal Support Workers (PSWs). Slip resistant footwear is known to reduce the risk of falls, however, it is difficult to predict how well a particular boot will perform prior to purchasing them. Our recently developed Maximum Achievable Angle (MAA) test can be used to rate footwear objectively to address this gap.OBJECTIVE:To rate the slip resistance of a selection of winter footwea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Our testing has shown that the MAA test is able to identify differences in slip resistance performance that the SATRA test is unable to find [ 19 ]. In fact, our findings have shown that slip resistance varies widely among commercially available winter footwear and that a new generation of slip resistant winter footwear that incorporates composite materials performs much better than most other footwear available on the market [ 20 , 21 ]. These advance materials have also been shown to perform better than conventional footwear in real-world conditions [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our testing has shown that the MAA test is able to identify differences in slip resistance performance that the SATRA test is unable to find [ 19 ]. In fact, our findings have shown that slip resistance varies widely among commercially available winter footwear and that a new generation of slip resistant winter footwear that incorporates composite materials performs much better than most other footwear available on the market [ 20 , 21 ]. These advance materials have also been shown to perform better than conventional footwear in real-world conditions [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 , 18 ]. A human-centred test method has been developed by researchers at KITE (Knowledge, Innovation, Talent, Everywhere)Toronto Rehabilitation Institute, University Health Network (KITE) to evaluate footwear slip resistance on ice surfaces [ 19 , 20 , 21 , 22 ]. Tests are done inside the WinterLab, which is one of KITE’s Challenging Environment Assessment Laboratories (CEAL).…”
Section: Introductionmentioning
confidence: 99%
“…WinterLab has a real ice floor that can reach sub-zero temperatures. The method, called the Maximum Achievable Angle (MAA) test, measures the steepest incline that participants can walk up and down while wearing test footwear without experiencing a two-foot slip [ 21 , 22 ]. The method can be performed on melting wet ice and smooth cold dry ice [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous snow boot research conducted slip resistance property evaluations under simulated conditions (Bagheri et al, 2019; Hsu et al, 2016). However, performance assessment of the snow boots on natural, operationally representative terrain is ultimately needed for successful development.…”
mentioning
confidence: 99%